Permasalahan Tanah Adat: Kesalahan dalam Komunikasi Pemerintahan atau Kegegalan Pesan Regulasi dan Kebijakan di Indonesia - Bambang Dwi Waluyo (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Protection of the rights of indigenous peoples in Indonesia has not been able to protect all of their rights. Although there have been many government products regarding the protection of indigenous peoples' rights in the form of 158 regional legal products on indigenous peoples, consisting of 11 provincial regulations, 57 regional regulations, 2 district head regulations, and 87 district head decisions. However, in reality there are still various conflicts and problems related to the rights of indigenous peoples. Using Ulber Silalahi's concept of government communication, this paper answers the question of how government communication influences regulations on indigenous peoples. However, what happens in Indonesia is not a mistake in government communication, but a failure of messages related to regulations and policies conveyed by the government as a sender to other receivers.